Uncal Herniation: Emergency Recognition and Multidisciplinary Operating Room, Nursing, Laboratory, and Radiology Management - Albalihed, Mohanad Mtrok H; Hadi Ali Hadi Tawhari; Khaled Awad Alenazi; Zakaria Hussain Alali; Faisal Abbad Alabbad; Khalid Lafi Al Hazmi; Ibrahim Mohammed Abddullah Safhi; Mohammed Hassan Alamri; Hadeel Ali mohammad Aljohany; Faisal Moussadif Aqeeli (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Uncal herniation is a life-threatening neurological emergency resulting from displacement of the medial temporal lobe through the tentorial notch due to critically elevated intracranial pressure (ICP). It often arises from traumatic brain injury, intracranial hemorrhage, tumors, or diffuse cerebral edema, and can rapidly compromise brainstem function and cerebral perfusion. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review the anatomical basis, pathophysiology, clinical presentation, diagnostic approach, and multidisciplinary management strategies for uncal herniation, emphasizing early recognition and intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">This comprehensive review synthesizes current evidence and clinical guidelines on uncal herniation, including anatomical considerations, etiologic factors, epidemiology, diagnostic imaging, and emergency treatment protocols. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Uncal herniation manifests with hallmark signs such as ipsilateral pupillary dilation, contralateral hemiparesis, and altered consciousness. CT imaging remains the first-line diagnostic modality for rapid identification of mass effect and midline shift. Immediate management focuses on ICP reduction through head elevation, controlled ventilation, hyperosmolar therapy (mannitol or hypertonic saline), and urgent neurosurgical intervention. Prognosis depends on timely recognition and reversal; reported reversal rates range from 50–75% when managed promptly. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Uncal herniation represents a final common pathway of uncontrolled intracranial hypertension and requires rapid, coordinated multidisciplinary care. Early detection and aggressive intervention are critical to prevent irreversible brainstem injury and improve survival outcomes.